The impact of fiscal rules on public finances: Theory and empirical evidence for the Euro area - Wim Marneffe; Bas van Aarle; Wouter van der Wielen; Lode Vereeck (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper presents a review of the most significant fiscal rules policymakers can choose from. The insights from this review are then applied to the current budgetary situation of the European Union. In the European Union, the supranational Stability and Growth Pact (SGP) should provide the necessary guidance in limiting governmental borrowing by member states. In addition to the SGP, European countries are implementing various other fiscal rules that bind central, regional and local governments. We provide empirical estimates of the effect of fiscal rules on fiscal balance, government spending and government revenues, using a Fiscal Rule Index. We find that fiscal rules have some effect on fiscal balances.
Keywords: F31; F41; G15; 330; euro area; fiscal policy; policy rules; fiscal sustainability; Finanzpolitik; Regelgebundene Politik; EU-Stabilitätspakt; Wirkungsanalyse; Öffentlicher Haushalt; Nachhaltigkeit; Eurozone